Smag for etik (Vol. 4):På sporet efter fødevareetikken - Christian Coff (Politik Ret & Samfund, 2006)
The interest in healthy food is ancient, and healthy eating habits have often been emphasized as a condition for a good life. No earlier ethics, however, contain deliberations as to man's attitude to the origin of the foods or to the system which has produced them. But food production was usually manageable. It no longer is. This is why the ethical field must now be expanded to include the responsibility for the production and choice of foods, and it is this foods ethic of which Christian Coff is on the scent. The book throws light on a key aspect of the difficulty in behaving responsibly today with a modern complicated production apparatus, and in this very way it helps us to do it. (Extract from Peter Kemp's preface to the book).